Sistem Pendukung Keputusan Berbasis Web untuk Menentukan Kelayakan Proposal Penelitian pada Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Muhammadiyah Purwokerto - Kholidun Kholidun; Tito Pinandita (JUITA : Jurnal Informatika, 2012)
Board of Research and Community Service (LPPM) is a board which concerns to direct and guide the lecturers to do a research to develop their scientific knowledge. This research is hoped to have a form of scientific knowledge that gives benefits to the development of social and economic within the society. There are three major kinds of the research in LPPM which are Hibah of Superior, Competitive and Study Program. The step of this research is conducted by proposing the proposal research into LPPM and then it will be given such an assesment based on criterias that have been determined. This research uses some research methods to find out a specific problem with the exact goal. The collecting data’s method has function to get data of the research, and the method of development system is used for designing process, examining, asessment, verification and also the decision result that appropiate with the data that has been received (appropiate with the expectation). The result of this study is implemented in a system of decision making to determine the eligibility of the research proposal in LPPM in Muhammadiyah University of Purwokerto. By adopting technology based on the web-site and architecture of client-server network, it enables the system of decision making can be accessed all at once. This system uses JSP programming language which is clustered with MySQL as its database